Studi Komparasi Antara Strategi Talking Stick Dengan Strategi Make A Match Terhadap Hasil Belajar IPASiswa Kelas IV SDN Kedungjenar Blora Tahun Ajaran 2015/2016 - Nugraheni, Ariska, Dra. Risminawati, M.Pd (2016)
Background problem of this research is the teacher has not yet be able to apply learning strategies that is suitable with the science learning. There are many other learning strategies that can be used to improve learning outcomes of science, such as Talking Stick strategy and Make a Match strategy. The aims of this study are to determine: (1) the difference of learning outcomes of science in using Talking Stick strategies and the Make a Match strategy in class four of state elementary school Kedungjenar Blora academic year 2015/2016. (2) the greater strategy that influences between Talking Stick strategy and the Make a Match strategy in learning outcomes of science class four of state elementary school Kedungjenar Blora academic year 2015/2016. This study is an experimental study. The subjects in this study are all four class students of state elementary school Kedungjenar Blora academic year 2015/2016. The techniques of collecting data that be used are the technique of tests and documentation. Test instruments are such as validity and reliability. The technique of analyzing data that be used is preceded by the t-test analysis which the prerequisites test are a test of normality and homogeneity test. Based on the results of data analysis with a significance level of 5% shows that there is obtained t>t table, namely 5,861>1,994 with the average value of science learning outcomes fourth grade A is greater compared the average value of science learning outcomes fourth grade B, ie 81.111>76.805. The conclusions of this study are as follows: (1) There are differences in learning outcomes of science in using the Talking Stick strategy and the Make a Match strategy in class four of state elementary school Kedungjenar Blora academic year 2015/2016, (2) Talking Stick strategy influences greater than the Make a Match strategy in learning outcomes of science class four of state elementary school Kedungjenar Blora academic year 2015/2016. Keywords: Talking Stick Strategy, Make a Match Strategy, Learning Outcomes.